Are the Notions of Leader–Member Exchange and Organisational Citizenship Effective in Enhancing Teachers’ Job Performance in Türkiye? A Moderated Mediation Model - Mehmet Sabir Çevik (Behavioral Sciences)
This study is correlational and cross-sectional quantitative research that examines the moderating role of working time with the school principal on the effect of leader–member exchange on teachers’ job performance through organisational citizenship. Data were collected from 481 teachers in 43 public schools across the western, central, northern, southern, and eastern regions of Türkiye using the convenience sampling method. The Leader–Member Exchange Scale, Organisational Citizenship Scale, and Employee Performance Scale were used as data collection tools. Data were analysed through descriptive analyses, Pearson correlation analysis, and moderator and moderated mediation analyses. The results indicated positive and significant relationships among leader–member exchange, organisational citizenship behaviours, and teachers’ job performance. It was found that leader–member exchange indirectly affected teachers’ job performance through organisational citizenship, and working time with the school principal served as a moderator in the relationship between leader–member exchange and organisational citizenship. The indirect effect of leader–member exchange on job performance through organisational citizenship was stronger for teachers with shorter working durations with the principal.